Mental health self-medication in psychiatry residents: from providing to seeking mental health care - Guízar-Sánchez, Diana; Yoldi-Negrete, María; Tovilla-Zárate, Carlos-Alfonso; Domínguez-Martínez, Tecelli; Robles-García, Rebeca; Fresán, Ana (Frontiers in Public Health, 2025)
ObjectiveThe purpose of the present study was to determine the prevalence of self-medication among psychiatric residents with self-reported mental disorders, and to study the factors associated with self-medication.MethodsA cross-sectional retrospective study was conducted with psychiatry residents who answered an online survey. Variables were compared between psychiatry residents who do and do not self-medicate to treat self-reported mental health problems. Those that differed in the bivariate analyses were included in a multivariate logistic regression model to identify those associated with self-medication.ResultsA total of 136 of the 330 psychiatry residents assessed comprised the final sample, 41.2% of which reported self-medication. Depression and anxiety were the most frequent mental health problems reported. Being verbally attacked (OR = 4.4), being in the last years of residency (OR = 4.2), being attacked by senior colleagues (OR = 3.7) and higher perceived discrimination (OR = 1.1) increased the risk for self-medication. Conversely, psychotherapy reduced the likelihood of self-medication (OR = 0.2).ConclusionSelf-medication is a common practice among psychiatric residents with mental disorders in Mexico. It is a major concern in psychiatry residents as it can cause symptom aggravation due to subjective medication. Health and educational institutions must protect residents from the risks of this practice by addressing the associated factors.